2010
DOI: 10.1051/radiopro/2010025
|View full text |Cite
|
Sign up to set email alerts
|

Implementation in ARGOS of ERMIN and AGRICP

Abstract: The ERMIN model is a new implement developed to enable estimation of the radiological consequences in inhabited areas of accidents in nuclear installations. Similarly, AGRICP is a model developed to enable estimation of the radiological consequences of contamination of agricultural production areas. This paper provides a short overview of the background of the two models and describes the features enabled through their implementation in the ARGOS decision support system. The integration allows calculation of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…The food chain and dose module FDMT of ARGOS (Hoe et al, 2002;Jacobsen et al, 2010) and JRODOS (Ievdin et al, 2010) has been analysed and a sensitivity analysis identified key parameters that contribute to the uncertainty of results. The database of the module was evaluated and those parameters that require modification identified.…”
Section: Main Achievements 21 Simulation Modelsmentioning
confidence: 99%
“…The food chain and dose module FDMT of ARGOS (Hoe et al, 2002;Jacobsen et al, 2010) and JRODOS (Ievdin et al, 2010) has been analysed and a sensitivity analysis identified key parameters that contribute to the uncertainty of results. The database of the module was evaluated and those parameters that require modification identified.…”
Section: Main Achievements 21 Simulation Modelsmentioning
confidence: 99%
“…Comprehensive decision support systems are available today (e.g. ARGOS 2 and JRODOS 3 ), intended for the assessment of environmental and radiological consequences for various scenarios involving atmospheric dispersion of fission products from nuclear facilities. It is challenging to estimate the individual radiation doses from radioactive fallout due to the numerous factors that influence the distribution of doses.…”
Section: Introductionmentioning
confidence: 99%
“…The DSS have been expanded over the years to include an increasing number of modules with specific functions for various ecosystems. The early atmospheric dispersion and deposition models had subsequent food chain contamination modules and dose calculations for humans, while some DSS now include modules for urban, forest and aquatic environments as well as countermeasures in various ecosystems, e.g., ERMIN (European Model for Inhabited Areas) and AgriCP (Agricultural Countermeasure Programme) (Raskob et al, 2010). In the event of radioactive fallout, there would be a subsequent transfer of radionuclides between different environmental compartments due to e.g., erosion, run-off, forestry and agricultural practice, and from rivers via estuaries to the marine ecosystems.…”
Section: Introductionmentioning
confidence: 99%